What is a Girl’s Experience of Physical Activity? A Qualitative Descriptive Study - Dickson, Caroline (Auckland University of Technology, 2008)
This qualitative study explores the experiences of female adolescents in relation to physical activity. The study investigates the experience of being adolescent and the meaning of a female adolescent’s experience of physical activity. A qualitative description with a phenomenological hue was the methodology used. Their perceptions of their lived experiences in relation to physical activity were revealed through stories. The participants were six adolescent females. The study data was gathered through open-ended questions and in-depth conversations, to seek meaning of the adolescent’s experience of physical activity. The interviews were transcribed and stories extracted from the data. Results from the findings of the study indicate that physical activity needs to be enjoyable for the female adolescent for her to be motivated to participate. What specifically constitutes enjoyment for the adolescent differs for each individual. The data also suggested that other persons of influence or the female adolescent’s environment may also have an impact on their participation. Peers, parents, their gender, body issues, competition, running, and certain restrictions were revealed as making a difference. For the female adolescent participating in physical activity, it would be advantageous to find an approach that allows a girl to experience physical activity in the way that works for her. Some participants, already good at sports, are likely to be very competitive, want to train hard, and will build friendships among their like-minded peers. These female adolescents are not so problematic. They already love physical activity and participate in it. The challenge is to target those female adolescents who do not participate on a regular basis, and to design successful interventions which promote and encourage them into physical activity. This change may prevent a further decline in the levels of physical activity for the adolescent who is at a stage when physical activity may be so advantageous.
Keywords: Exercise; Girls and sport; Sporting influences; Social interaction; Body image; Adolescent health